2012 XXXVIII Conferencia Latinoamericana en Informatica (CLEI) 2012
DOI: 10.1109/clei.2012.6427198
|View full text |Cite
|
Sign up to set email alerts
|

A methodology for preprocessing data for application of case based reasoning

Abstract: Produce quality software inside expected time and low cost has been one of the main challenges in the software industry today. Therefore, it is fundamental make estimates of size, effort, resources, cost and time spent in the software development process. Predictive models such as models based on analogy can be an alternative, especially in small and medium sized software development, they need perform reliable estimates. In this paper, we propose a methodology for pre-processing of data for use in software ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Richter and Weber (2013) concluded that cases should come from reliable sources. As a result, medical data pre-processing steps are the first and the foremost to improve the accuracy of CBR systems, which are based on EHR data (Borges et al, 2012). Data pre-processing step is achieved by integrating CBR with machine learning techniques (Gu et al, 2010), such as Artificial Neural Network (ANN), Fuzzy Logic, Genetic Algorithms (GA), and rough sets.…”
Section: The Evaluation Metricsmentioning
confidence: 99%
“…Richter and Weber (2013) concluded that cases should come from reliable sources. As a result, medical data pre-processing steps are the first and the foremost to improve the accuracy of CBR systems, which are based on EHR data (Borges et al, 2012). Data pre-processing step is achieved by integrating CBR with machine learning techniques (Gu et al, 2010), such as Artificial Neural Network (ANN), Fuzzy Logic, Genetic Algorithms (GA), and rough sets.…”
Section: The Evaluation Metricsmentioning
confidence: 99%